History and effects of immigration to the United States - Smith, Hallie M. (My University, 1908)
Introduction: “Immigration,” says R. Mayo Smith, “is the life history of the countries.” We can trace the different characteristics of a new nation such as the United States to the several sources from which the several parts of that nation come and yet they may be so changed by a different environment that the individuality of the several races is entirely lost.
Citation: Smith, Hallie M. History and effects of immigration to the United States. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Immigration; United States; Political Science; International Studies; Graduating theses; Senior theses; Theses